Services provided by project management consultant in Malaysian construction industry - Ismail, Dzulkarnaen (2005)
Project Management Consultant (PMC) has become an important entity in the construction industry and the use of its services has increased significantly in recent years. Even though PMC concept is relatively new in Malaysia, applied only after Malaysia had successfully completed the Petronas Twin Tower Project and the KL International Airport (KLIA Project), several issues related to failure of the PMC concept have been raised by the public and government. As a result of the many PMC failures highlighted by the mainstream media, the success of completed projects handled by Project Management Consultant had been overshadowed. This study is carried out to investigate the services provided by Project Management Consultant (PMC) in the Malaysian construction industry. A framework of PMC Services that suits the local construction environment was developed from the combination of three Project Management Consultantâ€™s Contract based on the case studied carried out. The study found that most of the services listed by the author were regarded by the respondents as â€œimportantâ€ services and should be carried out by the Project Management Consultants. The results of the survey for the level of satisfaction on the services provided by Project Management Consultant (PMC) show that the respondents had categorized the level of satisfaction under two main factors which are satisfied and fairly conducted